Deficits in volitional oculomotor control align with language status in autism spectrum disorders. Issue 1 (10th October 2012) - Kelly, David J.; Walker, Robin; Norbury, Courtenay Frazier
Abstract: Eye‐tracking paradigms are increasingly used to investigate higher‐level social and cognitive processing in autism spectrum disorder (ASD). However, the integrity of the oculomotor system within ASD is unclear, with contradictory reports of aberrant eye‐movements on basic oculomotor tasks. The purpose of the current study was to determine whether reducing population heterogeneity and distinguishing neurocognitive phenotypes can clarify discrepancies in oculomotor behaviour evident in previous reports. Reflexive and volitional eye‐movement control was assessed in 73 children aged 8–14 years from four distinct groups: Autism Language Normal (ALN), Autism Language Impaired (ALI), non‐autistic Language Impaired (LI) and Typically Developing (TD). Eye‐movement control was measured using pro‐ and antisaccade tasks and a novel 'search distracter' task to measure distractibility. Reflexive eye‐movements were equivalent across groups, but deficits in volitional eye‐movement control were found that aligned with language status, and were not specific to ASD. More than 80% of ALI and LI children presented error rates at least 1.5 SDs below the TD mean in an antisaccade task. In the search distracter task, 35.29% of ALI children and 43.75% of LI children had error rates greater than 1.5 SD s compared with 17.64% of ALN children. A significant proportion of children with neurodevelopmental disorders involving language function have pronounced difficulties suppressing reflexive saccades and maintaining fixations in the presence of competing stimuli. We extend the putative link between ALI and LI populations to non‐language tasks, and highlight the need to account for co‐morbidity in understanding the ontogenesis of ASD. Abstract : Eye‐tracking paradigms are increasingly used to investigate higher‐level social and cognitive processing in autism spectrum disorder (ASD). However, the integrity of the oculomotor system within ASD is unclear, with contradictory reports of aberrant eye‐movements on basic oculomotor tasks. The purpose of the current study was to determine whether reducing population heterogeneity and distinguishing neurocognitive phenotypes can clarify discrepancies in oculomotor behaviour evident in previous reports.